Bariatric Surgery Lowers the Risk of Major Cardiovascular Events - Brown, Andrew M; Yang, Jie; Zhang, Xiaoyue; Docimo, Salvatore; Pryo, Aurora D; Spaniolas, Konstantinos (Annals of surgery, 2022)
This study examines the impact of bariatric surgery on the risk of myocardial infarction, stroke, and a composite of cardiovascular outcomes in a large population cohort. Additionally, the impact of different bariatric surgery procedures on cardiovascular outcomes is assessed and compared.OBJECTIVEThis study examines the impact of bariatric surgery on the risk of myocardial infarction, stroke, and a composite of cardiovascular outcomes in a large population cohort. Additionally, the impact of different bariatric surgery procedures on cardiovascular outcomes is assessed and compared.Bariatric surgery has been shown to improve comorbid conditions that are associated with cardiovascular disease and death. Few large studies have examined the impact of bariatric surgery on cardiovascular outcomes, and specifically compared the different bariatric procedures.SUMMARY BACKGROUND DATABariatric surgery has been shown to improve comorbid conditions that are associated with cardiovascular disease and death. Few large studies have examined the impact of bariatric surgery on cardiovascular outcomes, and specifically compared the different bariatric procedures.A retrospective, observational, matched-cohort study was conducted in adult patients with obesity in New York state from 2006 to 2012. Patients were stratified into 2 groups, based on utilization of bariatric surgery. Patients were further subgrouped based on the types of primary bariatric surgery. The primary endpoint was the development of specific cardiovascular events - myocardial infarction (MI), and stroke; as well as a composite of both events.METHODSA retrospective, observational, matched-cohort study was conducted in adult patients with obesity in New York state from 2006 to 2012. Patients were stratified into 2 groups, based on utilization of bariatric surgery. Patients were further subgrouped based on the types of primary bariatric surgery. The primary endpoint was the development of specific cardiovascular events - myocardial infarction (MI), and stroke; as well as a composite of both events.A total of 328,807 patients, including 60,445 who had undergone bariatric surgery, and 268,362 matched nonsurgical controls were the study cohort for comparing surgical and nonsurgical patients. The risk of composite cardiovascular events decreased in the surgical group [hazards ratio (HR) = 0.48, 95% confidence intervals (CI): 0.45-0.51], as did the risk of MI (HR = 0.39, 95% CI: 0.35-0.42), and stroke (HR = 0.55, 95% CI: 0.51-0.59). Among the surgical cohort, sleeve gastrectomy patients had a higher risk of developing MI, stroke, and any type of cardiovascular event than gastric bypass patients.RESULTSA total of 328,807 patients, including 60,445 who had undergone bariatric surgery, and 268,362 matched nonsurgical controls were the study cohort for comparing surgical and nonsurgical patients. The risk of composite cardiovascular events decreased in the surgical group [hazards ratio (HR) = 0.48, 95% confidence intervals (CI): 0.45-0.51], as did the risk of MI (HR = 0.39, 95% CI: 0.35-0.42), and stroke (HR = 0.55, 95% CI: 0.51-0.59). Among the surgical cohort, sleeve gastrectomy patients had a higher risk of developing MI, stroke, and any type of cardiovascular event than gastric bypass patients.Bariatric surgery is associated with decreased risk of significant cardiovascular events compared to nonsurgical controls. In this exploratory analysis, gastric bypass was associated with a lower risk of all cardiovascular events than sleeve gastrectomy.CONCLUSIONSBariatric surgery is associated with decreased risk of significant cardiovascular events compared to nonsurgical controls. In this exploratory analysis, gastric bypass was associated with a lower risk of all cardiovascular events than sleeve gastrectomy.